Exploring Agile Methodologies in Software Development: A Systematic Review of SDLC Practices: Exploring Agile Methodologies in Software Development: A Systematic Review of SDLC Practices - Jaelani (Teknik Informatika, Universitas Pelita Bangsa, 2024)
This study aims to examine in depth the application of Agile methodology in the Software Development Life Cycle (SDLC). By focusing on the effectiveness, advantages, and limitations of Agile, this paper presents a comprehensive review of Agile's advantages over other SDLC models such as Waterfall, including relevant literature analysis. The findings show that Agile is effective for projects that require high flexibility, but has limitations on large-scale projects. The study also provides recommendations for the implementation of Agile in SDLC projects and suggests further research. Keywords: Agile, SDLC, Waterfall, software development, flexibility.